Individual water consumption indicators in households in the light of recent research conducted in Poland - Sierociński, Michał; Kwietniewski, Marian; Kowalski, Dariusz (Instal, 2025)
The article reviews the Polish literature on household water consumption surveys in Poland from the last 22 years. The purpose of the article is to demonstrate the need for cyclic surveys of these indicators nationwide, using a unified methodology, taking into account the size of settlement units, the type of development and the sanitary facilities of dwellings. Based on the review, the authors point out the progressive changes in the volume of unit water consumption in households and the lack of adaptation to these changes of the existing guidelines and legislation. The comparisons made were supplemented by the authors’ presentation of the results of their own research on water consumption in single – and multi-family households, conducted in a city of 20,000 people in southern Poland.
Keywords: households; water demand; unit indicators; review; 2000-2024